Forest structure and regeneration process of peat swamp Alan forests (Shorea albida) in Brunei Darussalam - Kobayashi, S. (1998)
Tropical peat lands constitute one of the most important area for the land utilization in insular Asia, although peat lands are widely distributed in Asia of 22.2 million ha compared with 5.2 million ha in America and 3.5 million ha in Africa (Kyuma et al. 1986). 18.2 million ha of peat exist in insular Asia. On the other hand, peat swamp forests are distributed 90,884 hectares in Brunei Darussalam. These forests dominantly consist of pure Shorea albida (Alan) stands classified into three forest types such as Alan Batu, Alan Bunga, Alan Padang (Anderson 1964). In this study, I tried to clarify the Alan forest structures and regeneration process at different site condition. Different forest type where observed from outside of peat dome to center such as the mixed swamp forest dominated Drybalanops rappa, Alan Batu, Alan Bunga, Alan Padang and Padan Paya forests. Among these forests, Alan forests occupied wide area and S. albida as monoculture stand is very peculiar in tropical rain forests associated with its phenological characteristics and site condition of peat swamp. Different Alan forest types are characterized on their heights and ground water levels. On the seedling establishment and regeneration process, although S. albida blossomed in February, 1986 in Brunei and Sarawak, the seedling population of S. albida almost dissapeared from the forest floor two year after. The main factors of mortality were considered to be the shortage of light intensity (less than 700 lux) and the water condition of the habitat which becomes easily dry on days without rainfall on the root system and becomes flooded after continual rainfall on the peat horizon. It is also appeared on the point of demography that the energy allocation pattern to root weight of S. angustifolia more than 30%. Peat land utilization must be taking into account of fragile ecosystem of S.albida forest on its regeneration process.